Helicity amplitude analysis of χ cJ → ϕϕ - Ablikim, M; Achasov, MN; Adlarson, P; Albrecht, M; Aliberti, R; Amoroso, A; An, MR; An, Q; Bai, XH; Bai, Y; Bakina, O; Baldini Ferroli, R; et al. (Springer, 2023)
Using (447.9 ± 2.3) million ψ(3686) events collected with the BESIII detector, the decays of χcJ→ ϕϕ (J = 0, 1, 2) have been studied via the decay ψ(3686) → γχcJ. The branching fractions of the decays χcJ→ ϕϕ (J = 0, 1, 2) are determined to be (8.59 ± 0.27 ± 0.20) × 10−4, (4.26 ± 0.13 ± 0.15) × 10−4, and (12.67 ± 0.28 ± 0.33) × 10−4, respectively, which are the most precise measurements to date. From a helicity amplitude analysis of the process ψ(3686) → γχcJ, χcJ→ ϕϕ, ϕ → K+K−, the polarization parameters of the χcJ→ ϕϕ decays are determined for the first time.